Cardiac resynchronization therapy is associated with improvement in clinical outcomes in Indian heart failure patients: Results of a large, long-term observational study - Naik, Ajay (Indian Heart J, 2018)
BACKGROUND: Heart failure (HF) is a common health problem in South Asia, and its incidence and prevalence are projected to rise. Cardiac resynchronization therapy (CRT) has been shown to improve mortality, reduce hospitalizations, and improve symptoms in selected patients with HF. The South Asian Systolic Heart Failure Registry (SASHFR) was designed to be a large and comprehensive registry of Indian HF patients with the purpose of enhancing the quality of care and clinical outcomes of HF patients by promoting the adoption of evidence-based, guideline-recommended therapies, in particular CRT. METHODS: Overall, 471 patients on optimized medical therapy and meeting CRT implantation guidelines were followed up in 12 Indian hospitals. During the 2-year follow-up period, clinical response in terms of clinical composite score, overall performance and changes in HF performance metrics, mortality and hospitalizations rates were evaluated. RESULTS: Of 471 patients, 116 (24.6%) accepted to be implanted with a CRT device, while 355 (75.4%) refused, financial constraints being the main reason for refusing a CRT device. The study met its primary outcome, as the number of patients associated with an improvement in clinical composite score at 24 months was significantly higher (69.1%) in the CRT group than in the no-CRT group (44.7%) [odds ratio = 2 (95% confidence interval 1.25–3.20), p = 0.004]. Also, changes in HF metrics, mortality and hospitalizations rates indicated a more favorable response among patients who underwent CRT. CONCLUSIONS: The results from the SASHFR registry show a clear superiority of CRT over optimal pharmacological therapy in terms of improvement in clinical conditions among HF patients. The low rate of CRT acceptance, in patients indicated to this therapy, highlights the need for new health-care policies to improve awareness about HF disease and its therapies and possibly to enhance financial coverage of indicated therapies.